2007
DOI: 10.1183/09059180.00010206
|View full text |Cite
|
Sign up to set email alerts
|

Blocking endothelin: breaking new ground

Abstract: Endothelin is one of a number of profibrotic cytokines and growth factors, along with transforming growth factor-b, connective tissue growth factor and tumour necrosis factor-a, thought to be involved in the pathogenesis of idiopathic pulmonary fibrosis (IPF) and other interstitial lung diseases characterised by fibrosis, including IPF-related pulmonary hypertension.A growing body of evidence has supported a mitogenic effect of endothelin on fibroblasts and demonstrated that endothelin can reduce collagen brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Although PH is a common comorbidity in patients with IPF, the endothelin system has also been implicated in the pathophysiology of IPF as endothelin-1 and associated cytokines contribute to fibrosis development by inducing fibroblast mitogenesis, reducing collagen breakdown, and inducing synthesis of extracellular matrix. 25 BUILD-1 (Bosentan Use in Interstitial Lung Disease) was an international, randomized, placebo-controlled trial evaluating bosentan for the treatment of IPF. 26 Patients were eligible for inclusion if they had been diagnosed with IPF in the previous 3 years but not in the past 3 months, had a baseline 6-minute walk distance (6MWD) between 150 and 499 m, and were on contraception if female; exclusion criteria included interstitial lung disease other than IPF, FVC <50% or ≥90% predicted, DL CO <30% predicted, residual volume ≥120%, PaO 2 <50 to 55 mm Hg, forced expiratory volume in 1 s (FEV 1 ) to FVC ratio <65%, hemoglobin concentration <75% of the lower limit of normal, or evidence of severe PH, heart failure, or other terminal illness.…”
Section: Endothelin-1 Is Involved In Regulation Of Vasoconstriction/ Dilation By Binding To Etmentioning
confidence: 99%
“…Although PH is a common comorbidity in patients with IPF, the endothelin system has also been implicated in the pathophysiology of IPF as endothelin-1 and associated cytokines contribute to fibrosis development by inducing fibroblast mitogenesis, reducing collagen breakdown, and inducing synthesis of extracellular matrix. 25 BUILD-1 (Bosentan Use in Interstitial Lung Disease) was an international, randomized, placebo-controlled trial evaluating bosentan for the treatment of IPF. 26 Patients were eligible for inclusion if they had been diagnosed with IPF in the previous 3 years but not in the past 3 months, had a baseline 6-minute walk distance (6MWD) between 150 and 499 m, and were on contraception if female; exclusion criteria included interstitial lung disease other than IPF, FVC <50% or ≥90% predicted, DL CO <30% predicted, residual volume ≥120%, PaO 2 <50 to 55 mm Hg, forced expiratory volume in 1 s (FEV 1 ) to FVC ratio <65%, hemoglobin concentration <75% of the lower limit of normal, or evidence of severe PH, heart failure, or other terminal illness.…”
Section: Endothelin-1 Is Involved In Regulation Of Vasoconstriction/ Dilation By Binding To Etmentioning
confidence: 99%
“…In the final article of this issue of the ERR, DU BOIS [17] introduces the ongoing studies of bosentan in interstitial lung diseases, including IPF, a severe progressive lung disease that is fatal in the majority of patients. As well as being a wellestablished pathogenic mediator in PAH, ET is As the papers in this issue of the European Respiratory Review demonstrate, clinical trials have and will continue to play an important role in developing evidence-based treatment strategies for pulmonary arterial hypertension, as well as extending the application of endothelin receptor antagonists to other endothelin-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that, in addition to providing symptomatic relief, bosentan can improve longterm outcomes in patients with PAH, and research is now focused on combining targeted therapies to further improve the outlook for patients with PAH. The management of PAH is not always straightforward and, before moving on to the potential for ET receptor antagonism in different indications, HOEPER and LAENGER [16] present details of challenging cases of PH.In the final article of this issue of the ERR, DU BOIS [17] introduces the ongoing studies of bosentan in interstitial lung diseases, including IPF, a severe progressive lung disease that is fatal in the majority of patients. As well as being a wellestablished pathogenic mediator in PAH, ET is AFFILIATIONS…”
mentioning
confidence: 99%
See 1 more Smart Citation